The Search for Roots: German-Polish Migrant Literature and the Dilemmas of Identity in the Works of Sabrina Janesch, Alexandra Tobor, and Matthias Nawrat - Palej, Agnieszka (Transfer. Reception Studies, 2019)
The literary texts of young German-speaking writers of Polish origin are examined in detail. The aim of the analysis is to answer the questions of how the selected authors treat the search for identity in the selected literary works., the role of the influence of ’old‘ and ’new‘ culture on the identity formation of migrants and the resulting consequences. The subject of the investigation are the novels Katzenberge (2010) by Sabrina Janesch; Sitzen vier Polen im Auto: Teutonische Abenteuer (2012) by Alexandra Tobor; and Die vielen Tode unseres Opas Jurek von Matthias Nawrat (2015).